Does School Viability Assessment is Really Matter towards Efficient Resource Allocations and Good Governance: A Situation Analysis of Public Sector Schools of Sindh Province - Hamzo Khan Tagar; Ali, Sheraz; Bijarni, Ghulam Ali; Nazir, Hira (Advances in Social Sciences Research Journal, 2020)
This study is to assess the viability status of educational institutions inthe Sindh region and understand the factors for increasing non-viable schools on the ground. The study further highlights the school viability challenges associated with evidence-based planning and de-allocating resources from dysfunctional institutions. The viability of school is the basic requirement for access to education for all and the ultimate goal is to the optimization of resources and laid foundation towards good governance and quality education in the greater public interest. The findings of this study can be used for by the planners, decision-makers, policy-makers and implementing authorities for evidence based planning to enhance the performance within stipulated time frame and given limited resources in the school education department in greater public interest which leads to destinations of SDGs 04 quality education for all in the region.